PELAKSANAAN SUPERVISI OLEH KEPALA MADRASAH MELALUI TIPE KEPEMIMPINAN DEMOKTRATIS - Hasanah, Uswatun; Moh. Aufani (IAIN Datuk Laksemana Bengkalis, Indonesia, 2024)
Educational supervision aims to continue to fix the problems that are being faced in education, in this case, especially in the learning process in order to achieve an educational goal. The actor in supervision activities who often interact with teachers is a school principal. How to carry out supervision, a leader is not the same as other leaders. This depends on the type or style of leadership. Based on this, research was conducted on MI Sabilul Huda II Duko Timur Larangan Pamekasan regarding the implementation of supervision by the madrasah head through democratic leadership which consisted of three research focuses namely: 1) How is the implementation of supervision by the madrasah head through democratic leadership at MI Sabilul Huda II Duko Timur Pamekasan Prohibition. 2) what are the supporting and inhibiting factors for the implementation of supervision by the madrasah head through democratic leadership at MI Sabilul Huda II Duko TimurLarangan Pamekasan. 3) What are the implications of implementing supervision by the head of the madrasa through democratic leadership at MI Sabilul Huda II Duko Timur Larangan Pamekasan.